Pengaruh Masa Kerja, Spesialisasi Audit Dan Komite Audit Terhadap Kualitas Audit (Studi Kasus Pada Perbankan Syariah Di Indonesia) - Fitriani, Rizka (IAIN Kudus, 2019)
The rise of fictitious financing carried out by unscruplous bank employees makes people doubt the truth of the contents of financial statements issued by banks. This can be bad for Islamic Banks in Indonesia that are developing rapidly. To prevent this from happening again and again, Islamic Banks can conduct periodic audits to anticipate fraud at Islamic Banks. This research aims to determine the effect of tenure, audit specialization and audit committee on audit quality both simultaneously and partially. The population in this research is all Islamic Banking in Indonesia amounting to 14 banks. While the sampling technique used was purposive sampling in the category of Islamic Banking which issued financial statements from 2014 – 2018 which produced 13 samples of Islamic Banks. This study uses multiple linier regression analysis method using IBM SPSS Statistics 24. From this research it can be concluded that simultaneously the variables of tenure, audit specialization and audit committee have a significant effect on audit quality. But only affect around 29,5%. partially, only audit committee has a significant effect on audit quality. While audit soecialization is removed as an indicator of audit quality because it is considered constant.